The Effect of Good Corporate Governance on The Firm Performance of Conventional And Sharia Companies (2018-2021) - Saleh, Suji Abdullah; Maryanti, Lilis; Hardika, Andhika Ligar (Indonesian Journal of Economics and Management, 2024)
Good Corporate Governance is a system that regulates the relationship between the role of the board of commissioners, the role of the board of directors, shareholders, and other stakeholders. Every company is expected to implement Good Corporate Governance, but some companies experience problems related to company performance and even experience losses, especially during the COVID-19 pandemic. This study aims to analyze the effect of good corporate governance including variables of the board of directors, institutional ownership, audit committee, and audit quality on company performance as measured by Return on Equity (ROE) and compare the results between conventional companies (LQ45 index) and sharia (JII index). This type of research is quantitative research with a research population, namely conventional and sharia companies listed on the Indonesia Stock Exchange for the period 2018 to 2021 with sampling using purposive sampling techniques. The data used is documentary data in the form of financial statements and annual reports. The analysis method used is panel data regression analysis and hypothesis testing, statistical test F (together) and statistical test t (partial) using Eviews 10 software. The results showed that the board of directors had a significant effect on the performance of Islamic companies but not conventional companies. In contrast, managerial ownership and audit committees have a significant influence on the performance of conventional companies but no effect on Islamic companies. Meanwhile, audit quality does not have a significant influence on both conventional and sharia companies.